1979
DOI: 10.1128/jb.138.3.762-769.1979
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis for colonial variation in Neisseria gonorrhoeae

Abstract: When the piliated colony types of Neisseria gonorrhoeae, which predominate in recent isolates, were nonselectively subcultured in vitro, they gave rise to large numbers of nonpiliated, avirulent colonial variants. Evidence is presented to show that most of this variation occurs after active growth has ceased and that the variation is sensitive to the action of deoxyribonuclease. We suggest that this variation is a result of transformation. A second variation in colonial morphology involved differing levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Previous work from several laboratories suggested a role for natural transformation competence in the genetic variability of PitE expression observed in N. gonorrhoeae (Norlander et al. 1979;Seifert et al, 1988, Gibbs et ai.. 1989)-In contrast, it was also shown that p//E variation readily occurred under conditions preventing DNA transformation, i.e.…”
Section: Pifin Variation In Coma-deficientn Gonorrhoeae Ms11mentioning
confidence: 97%
“…Previous work from several laboratories suggested a role for natural transformation competence in the genetic variability of PitE expression observed in N. gonorrhoeae (Norlander et al. 1979;Seifert et al, 1988, Gibbs et ai.. 1989)-In contrast, it was also shown that p//E variation readily occurred under conditions preventing DNA transformation, i.e.…”
Section: Pifin Variation In Coma-deficientn Gonorrhoeae Ms11mentioning
confidence: 97%
“…Owing to these properties, transformation has been invoked as a mechanism involved in pilus-specific colony variation of gonococci (Norlander et al, 1979). Conclusive evidence for the transformation model was recently provided by demonstrating a decreased frequency of pilus phase transitions in a DNA uptake deficient mutant and by growth of gonococci in the presence of DNase I Gibbs et al, 1989).…”
Section: Two Distinct Classes Of Iga Protease Precursorsmentioning
confidence: 99%
“…Autolysis and PG hydrolysis in N. gonorrhoeae are not only interesting from the point of view of bacterial physiology but may also be involved in genetic transformation and pathogenesis. Gonococci undergo natural transformation (Sparling, 1966), and the donor DNA is thought to be provided by lysed cells (Norlander et al, 1979;Seifert et al, 1988). Gonococci also release monomeric fragments of PG (Sinha and Rosenthal, 1980) that have multiple biological activities, including killing ciliated fallopian tube cells in the organ culture model of PID (Melly et al, 1984;Fleming et al, 1986;Krueger et al, 1987;Dokter et al, 1994).…”
Section: Introductionmentioning
confidence: 99%